The THE EFFECT OF TAX TREATY ON FOREIGN DIRECT INVESTMENT ACTIVITY: INDONESIA OVERVIEW - rofi cahyono (Fakultas Ekonomi Universitas IBA, 2022)
The effect of tax treaty on foreign direct investment (FDI) has attracted many researchers. However, all of the studies on the effect of tax treaty on foreign direct investment show ambiguous results depending on the approach used, the study's location, and the time studied. Moreover, the study about the impact of tax treaty on foreign direct investment is rare in Indonesia context. This study uses panel data analysis to investigate the effect of tax treaty and others FDI determinant on FDI in Indonesia. By using Gravity Model, this research conclude that tax treaty has a positive effect on FDI inflows in Indonesia. This research also conclude that the effect of tax treaty on FDI in Indonesia is grow over time. The result of tax treaty effect and age of FDI are consistent among FDI total and FDI by sectors. However, this research gives a mixed result on the effect of others FDI determinant on FDI Indonesia. The result varied by FDI sectors. Furthermore, in contrast with the effect of the tax treaty on FDI which significantly positive, the institutional factors gives insignificant result on FDI. The result is consistent by all sectors of FDI.